RADIKALISME PESANTREN: Studi terhadap Pesantren Darul Wahyain Magetan - Irsyadunnas Irsyadunnas (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
Quoting BNPT’s statement, there are at least 19 Islamic boarding school in Indonesia indicated to support the activities of radicalism and terrorism. Initially, the statement was based on several analytical factors, namely, the historical linkages of the post-conflict pesantren establishment, as well as the association of the founding figures with some organizations that allegedly taught the radical flow. Starting from this statement, it is urgent to do research on one of the radically categorized pesantren, namely Pesantren Darul Wahyain Magetan. The reason for the selection of this pesantren according to information that the authors get from various sources, there are no signs or real evidence on the ground indicating that the Pesantren is based radically. The existence of Pondok Pesantren Darul Wahyain in Magetan does not meet the criteria to be called a radical pesantren, as formulated by the experts, namely textual, unilateral truth claims, a priori with western, anti-secular and extreme. In relation to the curriculum it can be explained that in general, the curriculum applied in Pesantren Darul Wahyain is not all that directs his santri into radicalist or terrorist.